Seasonal Variations in the Histomorphology of Caprine Ovaries - Devi, Gayatri; Mishra, Girish Kumar; Pandey, Sriti; Asati, Abhishek; Singh, Abhiyuday Pratap; Ningwal, Deepak; Sharma, Mayank; Jamre, Ritika; Raghuvanshi, Pavan Divan Singh (The Indian Journal of Animal Reproduction, 2026)
The variation in the size of the dominant as well as subordinate follicle may be due to seasonal effect during breeding and non-breeding season in goats. Goat ovaries were collected from a local slaughter house during winter, summer and rainy season. The ovarian tissue sections were fixed with 10% neutral buffered formalin saline. Haematoxylin and Eosin staining was performed for histomorphological analysis of follicular and luteal tissues. The mean number of antral folli cle(s) was 1.33±0.21, 1.00±0.26 and 1.50 ± 0.34 during summer, rainy and winter season, respectively. The mean number of subordinate follicles during summer, rainy and winter season was 3.17±0.40, 2.17±0.31 and 3.00±0.52, respectively. A significantly higher (p
Keywords: Goat; Ovarian Follicles; Corpus Luteum; Seasonal Variation.